Teaching and learning with power and privilege: Student and teacher identity in education about gender-based violence. (August 2022) - Vanner, Catherine; Holloway, Allison; Almanssori, Salsabel
Abstract: Gender-based violence (GBV) is a global concern that disproportionately impacts girls and marginalized communities; there is a need to better understand public education's role in enhancing understanding of GBV. This study uses qualitative participatory methods to study the experiences of 14 Canadian teachers who teach about GBV. Participants struggled to balance teaching their most privileged students about GBV while protecting students more likely to have experienced it directly. Feminist pedagogy of GBV should utilize strategies and curriculum that are action oriented and rooted in both the systemic contexts of GBV and the intersectional lived experiences of students and teachers. Highlights: Teachers sought to enable students to recognize GBV's prevalence, root causes, and connections to other forms of inequity. Aspects of shared teacher-student identity created opportunities for enhancing student engagement and connection. Teachers emphasized reflexivity to grapple with power and privilege relating to their social locations and their students'. Focusing on students' counter-resistance could cause teachers to marginalize more vulnerable students. Less academically inclined students often excelled with action-oriented pedagogy to address difficult knowledge.